Developing Teaching Materials to Enhance Critical Thinking Skills through Group Investigation in Composite Functions - Apriliani, Anggun; Kania, Nia; Umar, Nasir (EDUPEDIA Publisher, 2025)
This study aims to develop Group Investigation (GI)-based teaching materials to enhance the critical thinking skills of vocational high school (SMK) students in understanding and solving problems related to composition functions. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research produced teaching materials validated by subject matter experts, ensuring their quality, relevance, and alignment with curriculum objectives. Through GI stages—grouping, planning, investigation, organizing, presenting, and evaluating—students not only deepened their understanding of composition functions but also developed critical thinking, problem-solving, and teamwork skills. The findings highlight contribute to the development of innovative teaching materials and provide a foundation for transforming mathematics education into a more practical and effective discipline, particularly for vocational students.